2011
DOI: 10.1007/s12011-011-9183-x
|View full text |Cite
|
Sign up to set email alerts
|

Permissible Value for Vanadium in Allitic Udic Ferrisols Based on Physiological Responses of Green Chinese Cabbage and Soil Microbes

Abstract: Greenhouse experiments were conducted to study the permissible value of vanadium (V) based on the growth and physiological responses of green Chinese cabbage (Brassica chinensis L.), and effects of V on microbial biomass carbon (MBC) and enzyme activities in allitic udic ferrisols were also studied. The results showed that biomass of cabbage grown on soil treated with 133 mg V kg(-1) significantly decreased by 25.1% compared with the control (P < 0.05). Vanadium concentrations in leaves and roots increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…In the agricultural soil, the total rape biomass was minimal (0.13 and 0.01 g, dry weight) at 297-397 mg V kg −1 , and no rape growth was observed at 647 mg V kg −1 . The inhibition of plant growth by elevated concentrations of V in soils agrees well with the previous finding that growth of green Chinese cabbage was inhibited in contaminated soils at V concentrations between 153 and 253 mg V kg −1 , and the growth of approximately 80 % of green Chinese cabbage plants decreased in soils at 553 mg V kg −1 (Xiao et al 2012) demonstrated that V inhabited alfalfa growth at 100 mg V kg −1 and the total biomass of alfalfa decreased by more than 95 % in soils exceeding 400 mg V kg −1 . We observed a significantly higher total biomass of rape planted in the mining soil (4.99 g dry weight) than in all agricultural soils, although the total V concentration in the mining soil was the highest in this study.…”
Section: The Influence Of Soil Vanadium On Rape Biomasssupporting
confidence: 90%
See 2 more Smart Citations
“…In the agricultural soil, the total rape biomass was minimal (0.13 and 0.01 g, dry weight) at 297-397 mg V kg −1 , and no rape growth was observed at 647 mg V kg −1 . The inhibition of plant growth by elevated concentrations of V in soils agrees well with the previous finding that growth of green Chinese cabbage was inhibited in contaminated soils at V concentrations between 153 and 253 mg V kg −1 , and the growth of approximately 80 % of green Chinese cabbage plants decreased in soils at 553 mg V kg −1 (Xiao et al 2012) demonstrated that V inhabited alfalfa growth at 100 mg V kg −1 and the total biomass of alfalfa decreased by more than 95 % in soils exceeding 400 mg V kg −1 . We observed a significantly higher total biomass of rape planted in the mining soil (4.99 g dry weight) than in all agricultural soils, although the total V concentration in the mining soil was the highest in this study.…”
Section: The Influence Of Soil Vanadium On Rape Biomasssupporting
confidence: 90%
“…The ability of rape to accumulate soil V in roots appeared to be comparably low, since the previously published root bioconcentration factors for woody and herbaceous plants were at least a level of magnitude higher (Table 4 ). For example, the root bioconcentration factors of Chinese cabbage estimated from total soil V and water-extractable V were 40 and 6983 %, respectively (Tian et al 2014;Xiao et al 2012) (Table 4). The root bioconcentration factors calculated from labile V in soils (HNO 3 extractable) were between 56 and 1080 % for Artemisia vulgaris, Polygonum cuspidatum, Phragmites australis, Rhus copallinum, Betula populifolia and Populus deltoides (Qian et al 2014).…”
Section: Vanadium Root Bioconcentration and Translocation Factors For Rapementioning
confidence: 99%
See 1 more Smart Citation
“…Parameters of isotherm models for the adsorption of V(Ⅴ) onto yellow cinnamon soil, manual loessial soil and aeolian sandy soil. 854.4 mg kg −1 and 748.6 mg kg −1 , respectively) were different from other soil types, such as German soils (range 1.7-143 mg kg −1 ), alliticudic ferrisols (130 mg kg −1 ) and Aluminum-pillared Bentonite (24.16 mg g −1 ) [6,17,47]. This was because of the specific surface area and the proportion of colloids in the adsorbent.…”
Section: Isothermal Adsorptionmentioning
confidence: 88%